Fostering Junior High School Students' Reading Comprehension of Narrative Texts through the Use of English-Medium Comics - I Putu Ngurah Wage Myartawan; Gusti Agung Ayu Parianingsih (Universitas Pendidikan Ganesha, 2011)
The research was aimed at improving the reading comprehension of the second graders of SMP N 2 Kediri by incorporating English-medium comics as teaching materials in teaching narrative texts. The study was a collaborative classroom-action research.